PENERAPAN PEMBELAJARAN KOOPERATIF TIPE NHT PADA SISWA SMP MENGGUNAKAN POWER POINT TERHADAP HASIL BELAJAR MATEMATIKA - WAHYUNITA, TRI (Universitas Pasir Pengaraian, 2016)
The purpose of this research was to increase the students Match teaching achievement, before and after doing the application of cooperative teaching model of Numbered Heads Together (NHT) type toward the eight grade students of SMPN 4 Rambah Samo academic year 2015/2016 with 20 students of heterogenic ability. This research has the low Match studying achievement as its background, where as the model of teaching was applied so far, by using direct teaching such as; lecturing method, exercises and giving tasks, and teaching process with teacher center. The teacher also never used Power Point teaching media for teaching Function lesson. The method of the research used was Collaborative Class Action Research including two cycles. The data collecting technique used in this research was analysis technique used by test technique and non-test technique. The non-test technique was done by using observation sheets. In this research was also analyzed the number of the students who has reached the KKM, the frequency distribution scores spreading and central tendency size by comparing the scores before doing class action and after doing class action which purposes to know whether there was an increasing on Match teaching achievement or not, before and after applying cooperative teaching of NHT type by using Power Point Media. The result of the data analysis shows that there was an increasing on the students Match studying achievement of eight grade students of SMPN 4 Rambah Samo.Key words : Â Â Â The application of cooperative teaching NHT type, the students Match teaching achievement